Math, asked by Anonymous, 11 months ago

In an A.P., the first term is -1 and eleven times the sum of the first three terms is equal to twice the sum of the next three terms. Find the common difference of the A.P.

Answers

Answered by RvChaudharY50
28

Solution :-

• A sequence is said to be in AP (Arithmetic Progression), if the difference between its consecutive terms are equal.

• The nth term of an AP is given as ;

T(n) = a + (n-1)•d , where a is the first term and d is the common difference.

• The common difference of an AP is given as ;

d = T(n) - T(n-1)

• If the number of terms in an AP is n ( where n is odd ) ,then there will be a single middle term.

Also, [(n+1)/2]th term will be its middle term.

• If the number of terms in an AP is n ( where n is even ) ,then there will be two middle terms.

Also, (n/2)th and (n/2 + 1)th terms will be its middle terms.

• The sum up to nth terms of an AP is given as ;

S(n) = (n/2)•[2a + (n-1)•d] where a is the first term and d is the common difference.

• The nth term of an AP is also given as ;

T(n) = S(n) - S(n-1)

we have,

First term = a = (-1)

→ Let common Difference = d

So,

11 * (sum of first three terms) = 2 * (sum of next three terms)

→ 11 * (a₁ + a₂ + a₃) = 2 * (a₄ + a₅ + a₆)

→ 11 * {a + (a + d) + (a + 2d)} = 2 * {(a + 3d) + (a + 4d) + (a + 5d)}

→ 11 * (3a + 3d) = 2 * (3a + 12d)

→ 11 * 3 * (a + d) = 2 * 3 * (a + 4d)

→ 11(a + d) = 2(a + 4d)

→ 11a + 11d = 2a + 8d

→ 11a - 2a = 8d - 11d

→ 9a = (-3)d

→ 9(-1) = (-3)d

d = (-9)/(-3) = 3 (Ans.)

Hence, the common difference of the A.P. is 3.

Answered by hukam0685
1

Step-by-step explanation:

Given:In an A.P., the first term is -1 and eleven times the sum of the first three terms is equal to twice the sum of the next three terms.

To find: Find the common difference of the A.P.

Solution:

First term of A.P. : a=-1

Common difference:d

Sum of first n terms=

S_n =  \frac{n}{2} [2a + (n - 1)d]\\  \\

Sum of first three terms

S_3 =  \frac{3}{2} [2( - 1) + 2d] \\  \\ S_3 = 3( d - 1) \:  \:  \: ...eq1

Now,

Sum of next three terms can be calculated using difference of sum of 3 terms from six terms

S_6 =  \frac{6}{2} ( - 2 + 5d) \\  \\S_6 = 3(5d - 2) \\  \\  S_{4 - 6} = S_6 - S_3 \\  \\  = 3(5d - 2) - 3(d - 1)  \\  \\  = 15d - 6 - 3d + 3 \\  \\S_{4 - 6} =  12d - 3 \:  \:  \: ...eq2\\  \\

ATQ

eleven times the sum of the first three terms is equal to twice the sum of the next three terms

11S_3 = 2S_{4 - 6} \\  \\

place the value from eq1 and eq2

11 \times 3(d - 1) = 2 \times (12d - 3) \\  \\ 33d - 33 = 24d - 6 \\  \\ 33d - 24d =  - 6 + 33\\  \\ 9d = 27 \\  \\ d =  \frac{27}{9}  \\  \\ d=3\\\\

Common difference is 3.

Hope it helps you.

To learn more on brainly:

1)The arithmetic sequence is 71,68, 65

Is 0 a term of the sequence

https://brainly.in/question/21137141

2)The first term of an arithmetic progression is 7 and the ratio of 8 and 15 term is 4 is 27 find the sum of first 25 term...

https://brainly.in/question/8145794

Similar questions